Effects of Climate Change on the Lives of Mountain Communities in Gilgit-Baltistan: A Case Study of Bubar village District Ghizer - Abid, Saira; Ahmed, Zubair; Ullah, Ehsan (Journal of Development and Social Sciences, 2025)
This study examines the local perceptions of climate change and its impacts on the socio cultural economic and psychological well being of residents in Buber valley Distrct Ghizer,Gilgit Baltistan. The valley a highly literate and agriculture dependent community experienced severe floods in 2022, highlighting its vulnerability to erratic rainfall glacier melt and other climate related hazards. A qualitative approach include in depth interviews focus group discussions and participant observation was employed to capture community experiences. Finding show that climate change has disrupted livelihoods agriculture water resources infrastructure education health and social cohesion leading to economic hardship trauma and displacement. The study recommends implementing disaster risk reduction strategies promoting sustainable agriculture and reforestration enhancing climate education and fostering collaboration with international institutions to strengthen long term resilence and adaptation in Buber valley District Ghizer.